2023
DOI: 10.1002/cncr.34731
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world retrospective study of KRAS mutations in advanced non–small cell lung cancer in the era of immunotherapy

Abstract: Background KRAS mutation‐positive (KRAS‐positive), advanced nonsmall‐cell lung cancer (NSCLC) is characterized by a poor prognosis. KRAS mutations are extremely heterogeneous from a biologic point of view, and real‐world data by mutation subtype in the era of immunotherapy are still incomplete. Methods The objective of this study was to retrospectively analyze all consecutive patients with advanced/metastatic, KRAS‐positive NSCLC who were diagnosed at a single academic institution since the advent of immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…All but one case had genetic alterations, including KRAS (5 cases), EGFR (3 cases), MET exon 14 skipping (1 case), and TP53 (1 case) mutations. Such profiles are similar to those reported in conventional invasive ADCs in Western countries and at our latitudes 3,13,19–21 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…All but one case had genetic alterations, including KRAS (5 cases), EGFR (3 cases), MET exon 14 skipping (1 case), and TP53 (1 case) mutations. Such profiles are similar to those reported in conventional invasive ADCs in Western countries and at our latitudes 3,13,19–21 …”
Section: Discussionsupporting
confidence: 88%
“…Such profiles are similar to those reported in conventional invasive ADCs in Western countries and at our latitudes. 3,13,[19][20][21] Based on the above findings, the described additional ancillary techniques were helpful to support the assessment of the required parameters and may be used in selected cases where mitotic count and/or definition of the extent of invasion (lepidic growth vs. papillary carcinoma in collapsed parenchyma) are problematic, though not strictly required for an optimal case stratification. As a matter of fact, in our series, the prevalence of selected LMP cases of resected stage I ADCs overlapped with that of the original paper, around 15% and in any case identified a subtype of lung cancers associated with a relatively favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our established tumor models and patient data reveal that in advanced disease, differences in KRAS mutant isoform-specific potency are no longer evident, mirroring findings from previous large cohort studies which failed to support KRAS-mutant allele-specific differences in outcomes 8,46,47 . KRAS mutant isoforms occur alongside distinct co-mutation patterns which ultimately affect signaling networks, immune surveillance and response to therapy 8,9 .…”
Section: Discussionsupporting
confidence: 72%
“…A real-world retrospective study revealed that the effectiveness of first-line ICIs, either alone or in combination with chemotherapy, did not differ among patients with different isoforms of KRAS mutations. Patients with KRAS-G12D and KRAS-G12A mutations showed a shorter median progression-free survival (mPFS), which did not reach statistical significance ( 40 ). The intermediate mechanism of immunotherapy for various KRAS mutation subtypes merits investigation.…”
Section: Discussionmentioning
confidence: 99%